Changes in the activity profiles of soccer players over a three-match training micro cycle - Andrzejewski, M.; Konarski, J. M.; Chmura, J.; Pluta, B. (International Journal of Performance Analysis in Sport, 2014)
The aim of this study was to investigate soccer players' recovery by analyzing activity profiles of 11 Polish professional league soccer players over a period of three intense matches. Activity profiles were collected to evaluate each player, who played 3 matches, within a period of 7 days. The Amisco Pro® system was used to collect these data. The total distance, 6 different motor activity intensity ranges, frequencies of different activities, recovery time, speed and some technical elements were observed. The average total distance was 11,286 m and players covered longer distances during every consecutive match. The players covered a greater distance in the 2nd half of the first and third matches. There was a systematic decrease in covered distance at the high speed running level, and an initial distance increase and decrease at the sprinting level. The findings of the study provide a detailed description of the physical demands placed on elite soccer players during short recovery periods, which will influence the way teams approach their training and preparation process, according to intense playing schedules.